2020
DOI: 10.1016/j.micromeso.2020.110221
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ZSM-5 zeolite crystal size on p-xylene selectivity in toluene disproportionation

Abstract: The effect of crystal size was explored in this work aiming at enhancing p-xylene selectivity through toluene disproportionation over ZSM-5 zeolite. The different physicochemical properties of ZSM-5 were investigated using various characterization techniques including X-ray diffraction (XRD), pyridine adsorption, Fourier transform infra-red (FTIR), BET surface area by N2 adsorption, inductively coupled plasma (ICP) and scanning electron microscopy (SEM). Each catalyst was tested in a fixed bed reactor at a tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…By comparing these UV‐vis DR spectra it becomes clear that the absorption bands are formed at a greater rate at 5 bar, indicating a higher conversion level at 5 bar. The higher pressure forces more reactants onto the catalytic active sites, therefore increasing the activity of the catalyst [37,38] . Furthermore, the intensity of the absorption bands is higher for the 20 : 80 SiO 2 5 bar reaction than for the 1 bar reaction as more polyaromatic species are formed due to a higher conversion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing these UV‐vis DR spectra it becomes clear that the absorption bands are formed at a greater rate at 5 bar, indicating a higher conversion level at 5 bar. The higher pressure forces more reactants onto the catalytic active sites, therefore increasing the activity of the catalyst [37,38] . Furthermore, the intensity of the absorption bands is higher for the 20 : 80 SiO 2 5 bar reaction than for the 1 bar reaction as more polyaromatic species are formed due to a higher conversion.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the catalytic conversion increased with increasing pressure, as the higher pressure enhanced the adsorption of the reactants on the active sites of the catalyst. Furthermore, the xylene selectivity decreased with increasing pressure, as more side reactions can occur when the pressure is increased [37,38] . These side reactions cause the formation of poly‐aromatic molecules, also known as coke molecules, that block the pores of the zeolite and cause deactivation [27,39,40] …”
Section: Introductionmentioning
confidence: 99%
“…Attempts are also made to selectively block the (010) surface or extension of sinusoidal channels along the a axis for enhancing shape selectivity. 93,94 Highly intergrown and twinned ZSM-5 crystals synthesized with NBA and tetrapropylammonium bromide (TPABr) as co-templates (Fig. 9F and G) exhibit a very high p-xylene selectivity (499%) (Fig.…”
Section: Aimed Control Of the Exposure Degree Of Crystal Facetsmentioning
confidence: 99%
“…44 Alternatively, xylene products may be formed by the disproportionation of toluene produced by the Scheme 2(iii) rearrangement mechanism (Scheme 2(iv)). 45,46 Cyclopentadienyl cations with ethyl or longer side chains may release light olefins through an internal rearrangement followed by elimination, as demonstrated for ethene in Scheme 2(v). 44…”
Section: Cycle 2aromatic Productionmentioning
confidence: 99%